2022
DOI: 10.1001/jamacardio.2022.2455
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Diagnostic Yield of Combined Cardiomyopathy and Arrhythmia Genetic Testing

Abstract: Key Points Question Does combined disease testing provide improved diagnostic yield and clinical utility for patients with a suspected genetic cardiomyopathy or arrhythmia? Findings In this cohort study of 4782 patients with a suspected genetic cardiomyopathy or arrhythmia, combined cardiomyopathy and arrhythmia testing revealed clinically relevant variants in 1 in 5 patients, and 66.0% of patients with positive findings had potential clinical management im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 65 publications
3
33
0
Order By: Relevance
“…Focused on genes associated with IAS (no more than 20 major genes -ACTC1, DSC2, DSG2, DSP, HCN4, FLNC, KCNH2, KCNQ1, LMNA, MYBPC3, MYH7, PKP2, PLN, RyR2, SCN5A, TNNI3, and TTN-, and no more than 100, including minor ones) (7), the technical approach to screen a large number of genes is not the limitation to date. It is widely accepted that increasing the number of genes imply a greater number of rare variants, remaining the most part without a conclusive role in IAS; however, a recent study has suggested that combined cardiomyopathy and arrhythmia genetic testing is able to identify a 10.9% gain in genetic diagnoses that would have been missed if testing had been limited to genes associated with a single cardiomyopathy or arrhythmia panel of genes (79,80). If clinical evaluation is included in genetic diagnosis, the diagnostic yield of molecular autopsy increases to nearly 35% (81).…”
Section: Genetic Analysis/interpretationmentioning
confidence: 99%
“…Focused on genes associated with IAS (no more than 20 major genes -ACTC1, DSC2, DSG2, DSP, HCN4, FLNC, KCNH2, KCNQ1, LMNA, MYBPC3, MYH7, PKP2, PLN, RyR2, SCN5A, TNNI3, and TTN-, and no more than 100, including minor ones) (7), the technical approach to screen a large number of genes is not the limitation to date. It is widely accepted that increasing the number of genes imply a greater number of rare variants, remaining the most part without a conclusive role in IAS; however, a recent study has suggested that combined cardiomyopathy and arrhythmia genetic testing is able to identify a 10.9% gain in genetic diagnoses that would have been missed if testing had been limited to genes associated with a single cardiomyopathy or arrhythmia panel of genes (79,80). If clinical evaluation is included in genetic diagnosis, the diagnostic yield of molecular autopsy increases to nearly 35% (81).…”
Section: Genetic Analysis/interpretationmentioning
confidence: 99%
“…As more genes have been identified, genetic testing yielding positive results for pathogenic mutations have been increasing. These diagnostic yields can potentially be further increased by also incorporating genetic testing for genes known to cause heritable arrhythmias with cardiomyopathy testing (14). Table 2 summarizes certain genetic syndromes with associated cardiomyopathies, and gene-targeted therapies.…”
Section: Genetic Basis Of Diseasementioning
confidence: 99%
“…Although immense progress has been made in elucidating the genetic determinants of HCM, much remains to be explored including genetic-, environmental- and epigenetic factors influencing disease penetrance and expressivity. Also, the rapid integration of genetic testing into everyday clinical practice has resulted in the identification of a large number of variants of uncertain significance, which cannot be acted upon clinically 10,13,14 . This issue is more evident in underrepresented populations, who are more likely to receive inconclusive genetic testing results, compared to well-studied European-ancestry HCM patients 15 .…”
Section: Introductionmentioning
confidence: 99%